Pola Asuh Orang Tua dalam Membangun Karakter Pendidikan Islam pada Anak di Lingkungan Masyarakat Dusun IV Jatimulya Kabupaten Karawang - Henti Putri Intan; Kasja Eki Waluyo; Tajudin Nur (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
Abstract: This research aims to determine parenting patterns that contribute to the formation of children's character in the Dusun IV Jatimulya community, Karawang Regency. The research method used is qualitative with field research type. Data was collected through in-depth interviews with parents and direct observation of parent-child interactions. Data analysis was carried out using qualitative analysis methods. The results of the research show that the parenting style applied by parents in Dusun IV Jatimulya has an important role in forming children's character. Factors such as open communication, authoritarian versus democratic parenting, and the application of moral and religious values ​​are key elements in forming a child's character. Apart from that, social environmental factors also influence the parenting patterns applied by parents. Keywords: Parenting Patterns, Children's Character, Community Environment, Dusun IV Jatimulya, Karawang Regency.